Efektivitas Komunikasi Pemasaran Terpadu PT. Bayou Berjaya Indonesia Pada Produk Snack “My Kripick” - Roemitha Marth; Mayasari, Mayasari; Oky Oxcygentri (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to determine and understand the implementation of integrated marketing communications carried out by PT. Bayou Berjaya Indonesia as a micro, small, and medium enterprise (MSME) in marketing the snack product "My Kripick". The theoretical framework used refers to the IMC (Integrated Marketing Communication) concept proposed by Kotler and Keller. This study uses a qualitative method with a descriptive approach where data collection is obtained through interview, observation, and documentation techniques. Informants in this study involved 4 people at PT. Bayou Berjaya Indonesia consisting of 1 business owner, 2 marketing and production employees, and 1 social media admin. The results of the study show that PT. Bayou Berjaya Indonesia has carried out several elements of IMC, namely advertising, sales promotion, personal selling, and events and experiences. The implementation of this strategy has been effective in accelerating the growth of the "My Kripick" product business, as evidenced by achievements such as being nominated for the Top 11 UKM (Small and Medium Enterprises) Food Award in the food and snack category from the Ministry of Trade of the Republic of Indonesia and the Top 10 MSME Onboarding Bank Indonesia 2023.